Return Seasonality in Stocks and Their Underlying Assets: Tax-Loss Selling Versus Information Explanations - Brauer, Greggory A; Chang, Eric C (Review of Financial Studies, 1990)
Results of tests contrasting tax-loss selling with intertemporal information variation as explanations of the January seasonal in stock returns are reported. Closed-end fund shares display the typical size-related January seasonal while their net asset values do not. Interpreting the net asset value return as a proxy for information about underlying assets, this result indicates information variation is not a necessary condition for the January effect in stocks. The share returns at the turn of the year are negatively related to their mean preceding year returns and positively related to the standard deviations of their preceding year returns. These results are consistent with tax-loss selling.